2021
DOI: 10.1002/hrm.22054
|View full text |Cite
|
Sign up to set email alerts
|

The double‐edged sword of job crafting: The effects of job crafting on changes in job demands and employee well‐being

Abstract: Job crafting is theorized to operate via changes that employees make to their work designs, yet this critical mechanism has remained scarcely tested. This study examined whether job crafting facilitates changes in two types of challenge demands, namely workload and job complexity, and hindrance demands and whether these changes explain why job crafting may have both positive and negative implications for employee well-being. We utilized a two-wave sample of 2,453 employees to examine the relationships between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 118 publications
(260 reference statements)
1
61
0
Order By: Relevance
“…The positive side of proactive behavior has been frequently discussed in prior literature, as shown in a meta-analysis by Thomas et al (2011) ; nevertheless, most of the current studies did not capture the potential negative effect of proactive behavior. Our research showed that subordinates’ relational crafting can also negatively influence their job well-being through increased work load, which fills the gap and echoes the suggestion of Harju et al (2021) to test the double-edged sword effect of job crafting.…”
Section: Discussionsupporting
confidence: 80%
“…The positive side of proactive behavior has been frequently discussed in prior literature, as shown in a meta-analysis by Thomas et al (2011) ; nevertheless, most of the current studies did not capture the potential negative effect of proactive behavior. Our research showed that subordinates’ relational crafting can also negatively influence their job well-being through increased work load, which fills the gap and echoes the suggestion of Harju et al (2021) to test the double-edged sword effect of job crafting.…”
Section: Discussionsupporting
confidence: 80%
“…Hauff et al argue that employee well-being is a key mechanism for organizational effectiveness. From the employee perspective, increasing different types of job demands may have positive effects on well-being, manifesting itself as work engagement (Harju et al , 2021). Also Schaufeli et al (2008) have previously theorized that work engagement represents one form of work-related well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Employees are inclined to choose tasks at which they will perform well and that are not too difficult (Elliot and Thrash, 2001). Approach crafting seeks to obtain and retain the positive aspects of work and gives employees an opportunity to demonstrate their competence (Elliott and Dweck, 1988;Harju et al, 2021). However, avoidance crafting occurs when employees try to avoid potential failure when handling certain tasks which may have them appear incompetent (Harju et al, 2021).…”
Section: Job Complexity and Approach/avoidance Craftingmentioning
confidence: 99%
“…Approach crafting seeks to obtain and retain the positive aspects of work and gives employees an opportunity to demonstrate their competence (Elliott and Dweck, 1988;Harju et al, 2021). However, avoidance crafting occurs when employees try to avoid potential failure when handling certain tasks which may have them appear incompetent (Harju et al, 2021). Thus, employees may avoid certain aspects of complex jobs while approaching others.…”
Section: Job Complexity and Approach/avoidance Craftingmentioning
confidence: 99%
See 1 more Smart Citation